The Role of Genes (and Environmental Stress) in Depression: An Update - F. Sharpley, Christopher (Current Psychiatry Reviews, 2011)
Objective: To review recent data on six previously-identified genetic associations with depression, focusing upon issues of samples and instruments, in order to clarify the roles of these genetic variables in depression. Methods: Search the literature from the last four years, tabulate studies and examine the presence of any recent trends. Results: At least one previously-identified genetic association with depression is subject to the confounding effects of agerelated dementia, and some others do not have recent supportive data that connect them to depression. In addition, over 300 other genetic factors have recently been identified to have associations with depression. Recent findings regarding one particular polymorphism (the ss 5-HTTLPR) suggest that the “causal” connection between some genes and depression may be via sensitivity to environmental stressors rather than as a result of the genetic predisposition per se. Conclusion: Recent genetic association studies of depression appear to suggest that some of the six previously-identified polymorphisms are not consistently related to depression, and that at least one major “causal” genetic variable may act via increased environmental sensitivity.
Keywords: Obsessive-Compulsive Disorder